Stable black phosphorus/Bi2O3 heterostructures for synergistic cancer radiotherapy. (July 2018) - Huang, Hao; He, Lizhen; Zhou, Wenhua; Qu, Guangbo; Wang, Jiahong; Yang, Na; Gao, Jie; Chen, Tianfeng; Chu, Paul K.; Yu, Xue-Feng
Abstract: X-ray induced photodynamic therapy (X-ray-PDT) is a promising approach for synergistic cancer radiotherapy and development of suitable radiosensitizers is highly desired. In this paper, we propose black phosphorus/Bi2 O3 (BP/Bi2 O3 ) heterostructures as efficient and biocompatible radiosensitizers for synergistic cancer radiotherapy. The heterostructures are synthesized by growth of ultrasmall Bi2 O3 nanoparticles onto BP nanosheets. The Bi2 O3 decoration inhibits the rapid degradation of BP nanosheets by occupation of the defect sites, and the synergistic effects of BP and Bi2 O3 enable 1 O2 overproduction under X-ray irradiation. This X-ray-PDT effect of the BP/Bi2 O3 nanosheets enhances the radiotherapy activity towards cancer cells by inducing cell apoptosis and cycle arrest. In vivo treatment of melanoma conducted on a clinical radiotherapeutic instrument demonstrates that the BP/Bi2 O3 sensitized radiotherapy inhibits tumor growth efficiently. Furthermore, the BP/Bi2 O3 nanosheets composed of biological friendly P, O, and Bi elements shows good biocompatibility in vitro and in vivo . This radiosensitizer thus has immense clinical potential for cancer therapy, and our findings reveal a general strategy to fabricate stable BP-based heterostructures for different applications.